A Doctor Across Borders Raphael Cilento and public health from empire to the United Nations - Cameron-Smith, Alexander (ANU Press, 2019)
In his day, Raphael Cilento was one of the most prominent and controversial figures in Australian medicine. As a senior medical officer in the Commonwealth and Queensland governments, he was an active participant in public health reform during the inter-war years and is best known for his vocal engagement with public discourse on the relationship between hygiene, race and Australian nationhood. Yet Cilento's work on tropical hygiene and social welfare ranged beyond Australia, especially when he served as a colonial medical officer in British Malaya and in the Mandated Territory of New Guinea. He also worked with the League of Nations Health Organization in the Pacific Islands and oversaw international social welfare programs for the United Nations. On one level, this professional mobility allowed ideas and practices of public health and government to circulate between colonial spaces of northern Australia, the Pacific Islands and Asia. On another, it meant that Cilento's Pacific colonialism and colonial experience shaped his understanding of Australian national health and welfare. Rather than attempt a comprehensive biography of Cilento, this book instead uses this border-crossing career as a means to explore several material and discursive facets of Australia's relationships to the Pacific and the world.